Investigating reproducibility in multiphase flow metrology: Results from an intercomparison of laboratories. (June 2021) - Elliott, A.J.; Falcone, G.; van Putten, D.; Leonard, T.; Haukalid, K.; Pinguet, B.
Abstract: This paper presents the results of an intercomparison of multiphase flow laboratories. Conducted as part of EMPIR project 16ENG07 – MultiFlowMet II, the primary focus of the investigation was to determine the influence of laboratory-specific factors on the reproducibility of measurements made by multiphase flow metres (MPFMs). To minimise these effects as much as possible, a portable transfer package was designed, including the MPFM, a transparent viewing section, and a straight pipe section with a length of 100 internal pipe diameters. A reproducibility parameter, ζ, was developed to quantify both the reproducibility of the transfer package. Across the three laboratories, metrological compatibility was achieved for the majority of test points. By presenting the ζ values as functions of the gas volume fraction (GVF) and water liquid ratio (WLR), it was possible to identify flow regimes that may be more susceptible to reductions in reproducibility. Highlights: Multiphase flow metrology vital for safe and sustainable use of complex oil fields. Affected by variations in laboratories, such as pipe geometry, gasses, and pressure. Intercomparison between three laboratories, using transportable transfer package. Reproducibility uncertainties all below 10%, often smaller. Challenges for measurement near phase transition; dependence on gas volume fraction.